An Analysis of Speech Functions in Spider-Man: No Way Home’s “I Lost Gwen” Scene - Anggraini, Putri Redni; Zega, Rio Ferdinand; Rangkuti, Linda Astuti; Sihite, Meida Rabia (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study analyzes the speech functions in the